Factors Associated with Recuding Blood Sugar Levels in DM Patients with Hyperglycemia in The Amaryllis Room of RSI PKU Muhammadiyah Pekajangan Pekalongan - W Wiruci; S Sugiharto (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Diabetes Mellitus is caused by autoimmune, decreased beta cell insulin secretion and other cause.Faktor that affect blood sugar levelsbin patient with Diabetes Mellitus include age,BMI and duration of diabetes. Objective:This study aims to determine the factors associated with the decrease in blood suger levels while in Diabetes Mellitus patients with hyperglycemia at RSI PKU Muhammadiyah Pekajangan Pekalongan. Sample:this study invoved all Diabetes Mellitus patients who were treated with hyperglycemia RSI PKU Muhamadiyah Pekajangan Pekalongan in 2019-2020 as may as 201 respondents. Methods: this study used a descriptive research methodwith a retrospective approach.Daya collection using medical records Results: the results showed that patients with diabetes mellitus had an average age of 58.13 years,BMI of 26.68kg/m2,duration of DMfor14.31 years,most of them were female (68.7%) and received the type of oral and injection combination therapy (91.5%).The results of the linear regression test showed that there was a significan relationship between age (p value 0.00) and length of suffering from DM (p value 0.00) with a decrease in blood suger levels in DM patients who were treated with hyperglycemia. There was no significan relationship between BMI (p value 0.79) with a decrease in blood suger levels while in DM patients who were treated with hyperglycemia. Conclusion: age and duration of suffering from Diabetes Mellitus are factors that influence the decrease in blood suger levels while in Diabetes Millitus patients who are treated with hyperglycemia at RSI PKU Muhammadiyah Pekajangan Pekalongan.Nurses need to provide education about risk foctor that cause hyperglycemia.